In situ encapsulation of Pt nanoparticles in mesoporous silica: synthesis, characterisation and effect of particle size on CO oxidation - Prashar, Atul K.; Mayadevi, S.; Rajamohanan, P. R.; Devi, R. Nandini (Applied Catalysis A-General, 2011)
Pt nanoparticles of narrow size distribution and average particle size of 4.4 nm are isolated exclusively inside SBA-12 mesoporous silica by a novel in situ method. The interaction of Pt precursor with surfactant-polymer composite micelle is followed by NMR and UV studies. The final Pt incorporated silica material is characterised by XRD, TEM and N(2) adsorption. The mesoporous nature of the silica is found to be intact after Pt incorporation without any pore blockage. CO oxidation activity of this material is compared with that of mesoporous silica incorporating different sizes of Pt viz., 1.8, 3.6 and 8 nm. Activation energies of CO oxidation for all these materials are calculated by a simple differential method based on first principles. A comparison of activation energies and single site yields reveals that these parameters are distinguishably less in catalyst containing 1.8 nm Pt nanoparticles but more or less same in catalysts containing 3.6, 4.4 and 8 nm Pt nanoparticles. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CO oxidation; In situ synthesis; Mesoporous silica; Pt nanoparticle